San Gregorio de Portoviejo University: 24 years of commitment to training professionals in Health Sciences - García, Mario A. (Revista Gregoriana de Ciencias de la Salud, 2025)
Last December, the Universidad San Gregorio de Portoviejo (USGP) proudly celebrated its 24th anniversary, marking almost a quarter of a century of contributions to the region and Ecuador's academic, scientific, and social development. In this context, we would like to dedicate this editorial to highlighting the growth and consolidation of careers in the ​​Health Sciences, pillars in the institution's history, and future projections.